2000
DOI: 10.1530/reprod/120.2.443
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis and testicular tumours in ageing dogs

Abstract: Spermatogenesis was examined in testes from 74 dogs of various breeds without clinically detected testicular disease. A modified Johnsen score system was used to determine whether spermatogenesis deteriorates with ageing. The diameter of seminiferous tubules was measured in dogs without testicular disease to examine other possible effects of ageing on tubular performance. There appeared to be no relation between age and these variables. The influence of testicular tumours on spermatogenesis was also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 10 publications
1
27
1
8
Order By: Relevance
“…A balance seems to exist between cell cycle inhibitors and inducers that in the normal in vivo situation keeps the cells quiescent. The residual proliferation capacity of Sertoli cells in vivo is probably the underlying reason for Sertoli cell tumors seen rarely in humans [41] and more often in dogs [42]. Mitotically active Sertoli cells have been found in testis nodules of infertile humans [43].…”
Section: Discussionmentioning
confidence: 99%
“…A balance seems to exist between cell cycle inhibitors and inducers that in the normal in vivo situation keeps the cells quiescent. The residual proliferation capacity of Sertoli cells in vivo is probably the underlying reason for Sertoli cell tumors seen rarely in humans [41] and more often in dogs [42]. Mitotically active Sertoli cells have been found in testis nodules of infertile humans [43].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is attributed to the secretion of excessive amounts of estrogen by the tumor cells (Nielsen and Kennedy 1990), leading to greater concentrations of estradiol in both testicular and peripheral venous blood (Peters et al 2000). It is known that gap junctions containing Cx43 in rodent myometrium can be altered by estrogen, through putative estrogen-responsive elements (Dahl and Berger 1978;Burghardt et al 1984;Yu et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The dog has been proposed as a model for studies of the male reproductive system, for example, in the development of testicular tumors (Peters et al 2000). In adult dogs, 5-15% of all neoplasms are testicular tumors (Grootenhuis et al 1990) with Sertoli cell tumors, seminomas, and Leydig cell tumors occuring with an about equal frequency (Nielsen and Kennedy 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, decreases in the number of germ cells and reduced seminiferous epithelium have been documented in aged humans (Zitzmann, 2013) and dogs (Lowseth et al, 1990). However, a previous study showed no relationship between ageing and the quality of spermatogenesis in the dog, judged by cellular assessment of the seminiferous tubule (Peters, de Rooij, Teerds, van Der Gaag, & van Sluijs, 2000). The discrepancy between the findings may be due to different criteria of evaluation or age classification.…”
Section: Age-related Aspects On Morphological Changes Of the Canine Tmentioning
confidence: 95%